The Ethics of Taxing Sugar-Sweetened Beverages to Improve Public Health - Goiana-da-Silva, Francisco (2020)
The World Health Organization highlights fiscal policies as priority interventions for the promotion of healthy eating in its Action Plan for the Prevention and Control of Non-communicable Diseases. The taxation of sugar sweetened beverages (SSBs) in particular is noted to be an effective measure, and SSBs taxes have already been implemented in several countries worldwide. However, although the evidence base suggests that this will be effective in helping to combat rising obesity rates, opponents of SSBs taxation argue that it is illiberal and paternalistic, and therefore should be avoided. Bioethical analysis may play an essential role in clarifying whether policymakers should adopt SSBs taxes as part of wider obesity strategy. In this article we argue that no single ethical theory can account for the complexities inherent in obesity prevention strategy, especially the liberal theories relied upon by opponents of SSBs taxation. We contend that a pluralist approach to the ethics of SSBs taxation must be adopted as the only suitable way of accounting for the multiple overlapping, and sometimes, conflicting factors that are relevant to determining the moral acceptability of such an intervention.